2010
DOI: 10.1364/oe.18.017504
|View full text |Cite
|
Sign up to set email alerts
|

Low loss and magnetic field-tunable superconducting terahertz metamaterial

Abstract: Superconducting terahertz (THz) metamaterial (MM) made from niobium (Nb) film has been investigated using a continuous-wave THz spectroscopy. The quality factors of the resonance modes at 0.132 THz and 0.418 THz can be remarkably increased when the working temperature is below the superconducting transition temperature of Nb, indicating that the use of superconducting Nb is a possible way to achieve low loss performance of a THz MM. In addition, the tuning of superconducting THz MM by a magnetic field is also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 22 publications
2
89
1
Order By: Relevance
“…Part of the goal of superconducting metamaterials, mainly focusing on the microwave frequency range, is to reduce the resonant losses and improve the resonance quality factor [128][129][130][131], since at low temperature superconducting materials possess superior conductivity than metals at frequencies up to low THz. It was found that the metamaterial resonance, including resonance strength and frequency, could be tuned by applying external dc or rf magnetic fields [132,133] in addition to changing the temperature. It has also been extended to the THz frequency range using high temperature superconducting (HTS) films [134,135], where THz radiation would not easily break Cooper pairs and the low temperature THz conductivity is still rather high enabling a strong THz metamaterial resonant response.…”
Section: Superconducting Metamaterialsmentioning
confidence: 99%
“…Part of the goal of superconducting metamaterials, mainly focusing on the microwave frequency range, is to reduce the resonant losses and improve the resonance quality factor [128][129][130][131], since at low temperature superconducting materials possess superior conductivity than metals at frequencies up to low THz. It was found that the metamaterial resonance, including resonance strength and frequency, could be tuned by applying external dc or rf magnetic fields [132,133] in addition to changing the temperature. It has also been extended to the THz frequency range using high temperature superconducting (HTS) films [134,135], where THz radiation would not easily break Cooper pairs and the low temperature THz conductivity is still rather high enabling a strong THz metamaterial resonant response.…”
Section: Superconducting Metamaterialsmentioning
confidence: 99%
“…16,17 To realize tunability in metamaterials, various approaches have been demonstrated to vary effective electromagnetic properties via laser light illumination, 17,18 external magnetostatic fields, 19 external bias voltages, 16,20,21 electrical or thermal effects in liquid crystals [22][23][24][25][26][27][28] and nonlinear effects of resonators or subtrates. 16,17,[29][30][31][32][33][34][35][36] Alternatively, structural reconfiguration is a novel and straightforward method for controlling the electromagnetic properties, including the amplitude, polarization and directionality of the metamaterial structures. The properties of metamaterials can be directly modified by reconfiguring the fundamental building block of the metamaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Superconductors, on the other hand, are intrinsically nonlinear materials, due to the extreme sensitivity of the superconducting state in external stimuli [7,8], which moreover exhibit significantly reduced Ohmic losses. They thus provide unique opportunities to the researchers in the field for the fabrication of superconducting metamaterials with highly controllable effective electromagnetic properties including wideband tuneability [9,10,11,12,13,14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Their operation frequency spans a huge range, from zero [51,52,53,54] to microwaves [55,18,56,19,32] and to Terahertz [11,12,37,57,38,39,40,15,58,59,41,42] and visible [45] frequencies. Moreover, researchers rely on particular superconducting devices to access the trully quantum metamaterial regime [30,60,61,62,63].…”
Section: Introductionmentioning
confidence: 99%